2009
DOI: 10.1007/s11547-009-0393-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of PET/CT in the detection of liver metastases from colorectal cancer

Abstract: Purpose. The aim of this study was to compare the diagnostic accuracy of 2-[fluorine-18] fluoro-2-deoxy-Dglucose positron emission tomography ( 18 F-FDG-PET) and computed tomography (CT) with PET/CT in the detection of liver metastases during tumour staging in patients suffering from colorectal carcinoma for the purposes of correct surgical planning and follow-up. Materials and methods. A total of 467 patients underwent a PET/CT scan using an iodinated contrast medium. We compared images obtained by the single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
0
8
0
6
Order By: Relevance
“…FDG-PET/CT was performed without injection of iodinated contrast media, as this is the standard technique at our institution. Some authors reported the technical feasibility of iodinated contrast-enhanced FDG-PET/CT, and this point deserves to be validated in the future and could possibly improve the results of FDG-PET/CT [22][23][24]. In follow-up, 64-slice CT in the portal and late phases was considered sufficient, in line with the current literature, even though the relevance of the latephase interest may be debated [7,25].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…FDG-PET/CT was performed without injection of iodinated contrast media, as this is the standard technique at our institution. Some authors reported the technical feasibility of iodinated contrast-enhanced FDG-PET/CT, and this point deserves to be validated in the future and could possibly improve the results of FDG-PET/CT [22][23][24]. In follow-up, 64-slice CT in the portal and late phases was considered sufficient, in line with the current literature, even though the relevance of the latephase interest may be debated [7,25].…”
Section: Discussionmentioning
confidence: 68%
“…Non abbiamo eseguito sequenze T2 pesate TSE short tau inversion recovery (STIR) dopo iniezione di SPIO, come riportato da Del Frate et al [19], dato che consideriamo l'effetto dello SPIO più evidente nelle sequenze T2 pesate GRE. La TC-PET-FDG è stata eseguita senza iniezione ev di mezzo di contrasto iodato come da nostro protocollo standard, alcuni autori hanno riportato la fattibilità tecnica della TC-PET-FDG con mezzo di contrasto iodato ed in futuro questo punto merita di essere rivalutato e dovrebbe migliorare i risultati della TC-PET-FDG [22][23][24]. Nel follow-up la TC con apparecchiatura a 64 detettori al tempo portale e tardivo è stata considerata performed according to current standards, with no US contrast medium being used, even though recent reports have shown a higher sensitivity compared with standard IOUS [18,26].…”
Section: Discussioneunclassified
“…In einer italienischen Studie an 467 Patienten mit KRK wies die kombinierte FDG-PET/CT bei der Detektion von Lebermetastasen eine Sensitivität und Spezifität von jeweils 98% auf und war damit der alleinigen CT (91% Sensitivität, 95% Spezifität) sowie der alleinigen FDG-PET (94% Sensitivität, 92% Spezifität) überlegen [14]. Obwohl einige Studien eine höhere Sensitivität von FDG-PET oder FDG-PET/CT für die Detektion pulmonaler Metastasen nahelegen (.…”
Section: Metastasierungunclassified
“…2,3,12,13 In rectal cancer where locoregional recurrences are more frequent than distant metastases, FDG PET/CT seems to have better accuracy than morphologic imaging, which could be misinterpreted in the presence of post-treatment scarring. 2,4 Assessment of Response to Treatment FDG PET/CT is emerging as the preferred method to assess the response to treatment in many types of cancer.…”
Section: Follow-upmentioning
confidence: 99%